Cavernous hemangioma of the rib mimicking malignant bone tumor: A case report - Mesfin Mulugeta, MD; Yenewub Muluken, MD; Raja Tamiru, MD; Ermias Gizaw Hailemeskel, MD; Bethelehem Nigussie, MD (Radiology Case Reports)
Intraosseous hemangiomas are benign vascular tumors which are more commonly seen in the vertebrae and skull but they rare in the ribs. Rib hemangiomas can mimic malignant rib lesions and definitive clinical and imaging diagnosis might be difficult and pathological confirmation will be required. Here we report a rib hemangioma in a 49-year-old male presented with painless chest wall swelling of 9 years duration, on chest CT scan the lesion showed dense radiating type calcification with cortical destruction. The patient was sent for core needle biopsy with the impression of chondrosarcoma, subjected to histopathology and confirmed to be a hemangioma. So, although rib hemangioma is rare it should be at the back of our mind for differential diagnosis of aggressive appearing rib lesions especially in patients presented with indolent, painless and incidental rib swelling.